2010
DOI: 10.1017/s0033291710001960
|View full text |Cite
|
Sign up to set email alerts
|

Patients with schizophrenia show increased aversion to angry faces in an associative learning task

Abstract: Background We were interested in examining the relationship between socially-relevant stimuli and decision processes in patients with schizophrenia. Methods We tested patients with schizophrenia and healthy controls on a stochastically-rewarded associative learning task. Participants had to determine through trial and error which of two faces was associated with a higher chance of reward. One face was angry, the other happy. Results Both patients and healthy controls were able to do the task at above-chanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 42 publications
(89 reference statements)
4
19
1
Order By: Relevance
“…Patients with schizophrenia also select angry faces less often than controls, given equivalent reward evidence [26]. In our study, increasing dopamine levels decreased this emotional bias in both PD groups.…”
Section: Discussionsupporting
confidence: 54%
“…Patients with schizophrenia also select angry faces less often than controls, given equivalent reward evidence [26]. In our study, increasing dopamine levels decreased this emotional bias in both PD groups.…”
Section: Discussionsupporting
confidence: 54%
“…Therefore, it might have been difficult to clearly categorize neutral faces in our task. In general, our results are consistent with previous reports showing that prior expectations influence decision making (Summerfield & Egner, 2009; Evans et al 2011). However, previous studies have shown this effect with gabor patches (Summerfield & Koechlin, 2008) or non-emotional faces (Summerfield et al 2006), whereas we reproduced such an effect, for the first time, with emotions.…”
Section: Discussionsupporting
confidence: 93%
“…Efficient reinforcement learning must rely on determination of not only the potential salience of environmental events (as would be demonstrated by a main effect of salience) but also how this salience changes contextually (as would be demonstrated in this instance by a salience-by-performance interaction). That this effect is not evident in individuals with schizophrenia provides further physiological support for reinforcement learning deficits in these individuals (Evans et al, 2011; Maia and Frank, 2011). …”
Section: Discussionmentioning
confidence: 92%